Collaborative Style Used by Transgender Women in Indonesia - Fhadilah Fitri Aviandasari; Eddy Setia; Thyrhaya Zein (BIRCU, 2022)
This study aims to analyze the speaking style used by transgender women in Indonesia. This style of conversation was analyzed using the theory of conversational analysis and the theory of conversational style between genders. The data sources in this study are five videos from Youtube channels of Patricia Gouw, Boy William, The A6, Karin Novilda, and Daniel Mananta Network. While the data in this study are the utterances made by transgender women in the video. This study uses a qualitative descriptive method by applying documentation techniques. After the data was analyzed, it was found that the conversation style used by transgender women in Indonesia is collaborative style. The collaborative style is obtained from the type of conversation structure used by Indonesian transgender women, such as adjency pairs, turn-taking, feedback, opening and closing conversations. These types of structure are in line with the conversation style performed by women who also doing cooperative speaking style, waiting for their turn to speak or when overlapping in their conversations but still with a supportive purpose. The overall findings refer to a conclusion that Indonesian transgender women use a collaborative style because they want to show that they are not offensive and easy to approach since they are a minority group who wants to be well accepted in society. This conversation style also has similarities with the conversation style used by women.